Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae) - Qi, Mujie (Zootaxa, 2016)
The genus Minooa Yamanaka, 1996 was monobasic with Minooa yamamotoi Yamanaka, 1996 as the type species. Previously, the genus was only recorded from Japan (Yamanaka 1996; Yamanaka & Yoshiyasu 2013). The diagnostic characters of this genus are as follows: antenna of male ciliated ventrally, simple in female; forewing M1 stalked with R3+4+5 for short distance, M2 and M3 stalked for 1/4 length; hindwing with Rs and M1 stalked, M2 and M3 stalked for 1/4 length; male genitalia with a long process arising from base of sacculus; aedeagus with several thorn-shaped cornuti; female genitalia with ductus bursae broadened and wrinkled posteriorly; signum formed by minute sclerites.